Customized Toric Intraocular Lens Implantation in Eyes with Cataract and Corneal Astigmatism after Deep Anterior Lamellar Keratoplasty: A Prospective Study - Domenico Schiano Lomoriello; Giacomo Savini; Kristian Naeser; Rossella Maria Colabelli-Gisoldi; Valeria Bono; Augusto Pocobelli (Journal of Ophthalmology)
Purpose. To investigate the effectiveness of toric intraocular lenses (IOLs) for treating corneal astigmatism in patients with cataract and previous deep anterior lamellar keratoplasty (DALK). Setting. San Giovanni-Addolorata Hospital, Rome, Italy. Design. Prospective interventional case series. Methods. Patients undergoing cataract surgery after DALK for keratoconus were enrolled. Total corneal astigmatism (TCA) was assessed by a rotating Scheimpflug camera combined with Placido-disk corneal topography (Sirius; CSO, Firenze, Italy). A customized toric IOL (FIL 611 T, Soleko, Rome, Italy) was implanted in all eyes. One year postoperatively, refraction was measured, the IOL position was recorded, and vectorial and nonvectorial analyses were performed to evaluate the correction of astigmatism. Results. Ten eyes of 10 patients were analyzed. The mean preoperative TCA magnitude was 4.92 ± 1.99 diopters (D), and the mean cylinder of the IOL was 6.18 ± 2.44. After surgery, the difference between the planned axis of orientation of the IOL and the observed axis was ≤10° in all eyes. The mean surgically induced corneal astigmatism was 0.35 D at 20°. The mean postoperative refractive astigmatism power was 1.13 ± 0.94 D; with respect to preoperative TCA, the reduction was statistically significant (p<0.0001). The mean change in astigmatism power was 3.80 ± 1.60 D, corresponding to a correction of 77% of preoperative TCA power. Nine eyes out of 10 had a postoperative refractive astigmatism power ≤ 2D. Conclusions. Toric IOLs can effectively correct corneal astigmatism in eyes with previous DALK. The predictability of cylinder correction is partially lowered by the variability of the surgically induced changes of TCA. This trial is registered with NCT03398109.